Pengaruh Pemberian Kacang Hijau Terhadap Peningkatan Hemoglobin Pada Ibu Hamil Di Wilayah Kerja Puskesmas Sambau Kota Batam Tahun 2023 - Heriyanti Heriyanti; Desi Ernita Amru; Nurul Huda (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
World Health Organization 4.5% of 149/100.00 maternal deaths worldwide are caused by anemia. One of the indirect causes of maternal death is anemia. Anemia is a condition where hemoglobin levels decrease below normal limits. The general aim of this research is to find out whether there is an effect of giving green beans on increasing hemoglobin in pregnant women in the Sambau Community Health Center Working Area, Batam City. This type of research is a quasi-experimental design with a pre-test post-test with control group design. The sampling technique used was purposive sampling with a total sample of 32 pregnant women, 16 pregnant women in the intervention group and 16 in the control group. Each respondent was given treatment by administering 500 ml of green beans, 2 times a day for 7 days. Hemoglobin levels were measured twice, namely pre-test before being given green beans and post-test after being given green beans. The results of the analysis using the Independent T Test analysis showed that the mean difference between the intervention group and the control group was 0.86, which means the average hemoglobin in the intervention group was greater than the average hemoglobin in the control group. And data obtained sig(2-tailed) 0.000 <0.05, which means there is an effect of giving green beans on increasing hemoglobin in pregnant women. It is hoped that health workers can apply green beans to pregnant women to increase Hb levels.?